IMPLEMENTASI PEMBELAJARAN MAHFUDZOT DALAM PEMBINAAN KARAKTER ISLAMI SANTRI DI PONDOK PESANTREN MAWARIDUSSALAM - Qory Dholi Syuhada. MS; Mahariah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Given the increasingly widespread development of the times that can be seen through electronic or non-electronic media, which can ultimately give the impression of a nation that is increasingly experiencing a prolonged crisis of ethics and trust. This research aims to be able to find out the efforts to form the Islamic character of students in learning, as well as knowing the supporting and inhibiting factors of efforts to form the Islamic character of students through learning mahfudzot at MTS Mawaridussalam Islamic boarding school. The method used in this research is qualitative research, through the process of interviews, observation, and documentation. The data analysis technique in the research uses a technique consisting of three stages, namely data reduction, data display, and also conclusion drawing. The results of the study found that the implementation of Mahfudzot learning in fostering the Islamic character of students at the Mawaridussalam Islamic boarding school uses storytelling, memorization, and singing strategies. The supporting factors found in the implementation of Mahfudzot learning are the high motivation of the students and competent teachers. As for the inhibiting factor, it is the laziness that occurs by the students. The conclusion in the study states that the implementation of Mahfudzot learning in fostering the Islamic character of students at the Mawaridussalam Islamic boarding school can be categorized as good in accordance with the standard provisions of the theory that has been described with the help of adapted source material.